1993
DOI: 10.1016/0165-2427(93)90022-v
|View full text |Cite
|
Sign up to set email alerts
|

Early phenotypic and functional alterations in lymphocytes from simian immunodeficiency virus infected macaques

Abstract: Kneitz, c., Kerkau, T., Müller, J., Coulibaly, C., Stahl-Hennig, c., Hunsmann, G., Hünig, T. and Schimpl, A., 1993. Early phenotypic and functional alterations in Iymphocytes from simian immunodeficiency virus infected macaques. Veto Immunol. Immunopathol., Phenotypic and functional changes in Iymphocytes from rhesus monkeys (Macaca mulatta) were investigated during the first 6 months after infection with SIVmac 32H. Animals preimmunized with keyhole !impet hemocyanin (KLH) were sacrificed 1. 3, 6, 12, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
(13 reference statements)
1
13
0
Order By: Relevance
“…To assess the clinical consequences of the SHIV challenge, the percentage of CD29 ϩ CD4 ϩ lymphocytes was determined, since a drop in this population is an early prognostic marker for a decline in immune function in humans (4,8) and macaques (17,22). A transient decline in the percentage of CD29 ϩ CD4 ϩ cells was observed in SHIV-infected control monkeys during the acute phase of infection but not in the vaccinated macaques (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the clinical consequences of the SHIV challenge, the percentage of CD29 ϩ CD4 ϩ lymphocytes was determined, since a drop in this population is an early prognostic marker for a decline in immune function in humans (4,8) and macaques (17,22). A transient decline in the percentage of CD29 ϩ CD4 ϩ cells was observed in SHIV-infected control monkeys during the acute phase of infection but not in the vaccinated macaques (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with those of other studies in the FIV and simian immunodeficiency virus (SIV) systems. 33,34,50,72 In addition, selective depletion of CD4-bearing thymocytes has been observed in HIV-infected adults and in children. 6,8,58,67 As with FIV infection, the severely depleted thymic tissue from children dying of AIDS contained minimal evidence of virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29] and seven SPF weanling age cats (Nos. [30][31][32][33][34][35][36]. The FIV infection status and disease course of these animals has been previously described and is briefly summarized in Table 1.…”
Section: Animals and Sample Collectionmentioning
confidence: 99%
“…Not only in humans, but also in the macaque model, it was shown that immune activation played a crucial role in lentiviral pathogenesis. The infection with simian immunodeficiency viruses (SIV) is usually apathogenic in the natural hosts like sooty mangabeys or African green monkeys [14, 15], whereas the infection of rhesus macaques with pathogenic SIV strains resembles the progressive course of human HIV-1 infection [16]. Pathogenic and apathogenic lentiviral infections are characterized by comparable viral loads in acute and chronic phases of the disease and a similar degree of CD4+ T cell destruction in cell culture [7].…”
Section: Beyond Hivmentioning
confidence: 99%